MULTINATIONAL ENTERPRISES IN AN INTEGRATED GLOBAL ECONOMY: A CHALLENGE FOR TRANS-NATIONAL TRADE UNIONS COOPERATION - Buccella, Domenico (Revista Venezolana de Análisis de Coyuntura, 2016)
Up to its current stage, globalization seems to have led to a process of growing economic integration which has allowed for an increase in the volume of regional and international trade as well as for an increase in the degree of regionalization and internationalization of capital mobility. Multinational Enterprises (MNEs), by moving capital around the world, are able to capture global advantages putting labor markets under pressures and creating the possibility that governments and trade unions engage in a "race to the bottom” regarding the regulation of labor standards and conditions. This work reviews the relevant literature on the strategic interaction between MNEs and trade unions within the spheres of international trade and production. Role, strategies and challenges that trade unions have to face in the next future, both at the regional (European) and global level are analyzed. Keywords: Globalization, Multinational Enterprises, international trade and production, international trade unionism.